2016
DOI: 10.1016/j.ajodo.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Conservative orthodontic fixed appliance management of pediatric mandibular bilateral condylar fracture

Abstract: Conservative treatment of a mandibular fracture by fixed orthodontic means is a viable treatment option that is relatively straightforward and cost-effective and has a high level of patient acceptance and comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
(43 reference statements)
1
24
0
3
Order By: Relevance
“…Good occlusion with masticatory function is conducive to remodeling 15,27 of imperfectly aligned fracture segments into satisfactory anatomic and functional positions within the limits of the functional matrix principle 28 . Andrew et al 6 discussed that during the mixed dentition stage, ORIF should be reserved for situations in which the occlusion is not improving because of a greater tolerability of imperfect alignment 6,13,15,20,27 when the treatment goals are achieved, similar to displaced subcondylar fractures in children less than 12 years of age 5,12‐14,17,26,29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Good occlusion with masticatory function is conducive to remodeling 15,27 of imperfectly aligned fracture segments into satisfactory anatomic and functional positions within the limits of the functional matrix principle 28 . Andrew et al 6 discussed that during the mixed dentition stage, ORIF should be reserved for situations in which the occlusion is not improving because of a greater tolerability of imperfect alignment 6,13,15,20,27 when the treatment goals are achieved, similar to displaced subcondylar fractures in children less than 12 years of age 5,12‐14,17,26,29 …”
Section: Discussionmentioning
confidence: 99%
“…However, two significantly displaced fractures in this study were managed conservatively ‐ they showed step deformity at 4 weeks follow‐up and complete remodeling without any contour defects after 18 months. The exceptional remodeling potential of children has already been widely accepted for cases with displaced condylar fractures except for extreme dislocations 6,12,14,26 . Alpen 13 also reported a case of complete remodeling overcoming malunion deformities and criticized Posnick et al’s belief of “unpredictable remodeling potential of pediatric craniofacial skeleton resulting in malunion and contour deformities if fractures were not reduced and fixed anatomically” 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,21 Disruption of the condylar growth center with dissection or fixation often results in facial skeletal deficiency (class II skeletal malocclusion or facial asymmetry) and can cause negative, long-term, functional and aesthetic sequelae. 2,30,31 This, combined with the aforementioned risks of open techniques and inconsistent results of ORIF in the literature, 10,19,32 has led us to utilize closed reduction for the treatment of pediatric and adult subcondylar fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological signs of resorption were observed in patients with detachment of the lateral pterygoid muscle from the proximal fragment (53) and the number of patients experiencing condylar resorption following open reduction can be as high as 100% (11). However, other authors point out that conservative therapy with MMF produces very good treatment results in children and adolescents (50,54).…”
Section: Diagnosis Of Mandibular Condyle Traumamentioning
confidence: 99%